ASPECTS CONCERNING EXTERNAL PARTNERSHIPS OF ROMANIA AFTER THE SECOND WORLD WAR - Popa, Florina (Studies and Scientific Researches. Economics Edition, 2019)
Abstract After the ending of the Second World War, Romania's cooperation relations with other countries were subordinated to the political and economic situations developed among the world states and to the events that followed the completion of the war, the form and content of these relations being different, corresponding to the context.The study presents aspects related to the partnership relations developed through the economic cooperation relations achieved by Romania within the Commission for Reciprocal Economic Aid – COMECON (CAER), on the period of  its operation (1949-1989).There are presented participants' cooperation modalities, the partnership being of                    public-public or public-private type.The examples shown include elements regarding the participating parties, the objectives to be achieved, the period, participation share, as the case may be.Also, some references are made to the enlargement of Romania's economic cooperation relations, internationally, after the 1970 year, expression of the favorable evolution of the geographical space of manifestation of the Romanian foreign trade.